External and internal training load relationships in soccer players: the metabolic power approach - Eser Çalı; Utku Alemdaroğlu; Yusuf Köklü; Harun Türkdoğan; Gökhan Çiçek; Alper Aşçı (Asociación Española de Ciencias del Deporte, 2020)
The aim of the present study was to examine the relationships between internal training loads (TL) (Banister, Edwards Training-Impulse (TRIMP), session RPE (s-RPE)) and external TL (Total distance (TD), high speed distance (HSD),  high metabolic distance (HMD) in amateur soccer players.  Nine male amateur soccer players (age = 28.74±5.2 years; height 173.74± 8.04 cm; weight 72.73±5.5 kg) voluntarily participated in the study. Individual field-based training sessions were monitored over 8 weeks. The results showed that there were moderate and very large correlations between s-RPE and both Edwards and Banister's TRIMP (respectively, r = 0.42-0.86; r= 0.45-0.85). Additionally, from large to nearly perfect correlations were observed between the HR-based methods (r= 0.58-0.98). We also found moderate to very large correlations between s-RPE and HMD and large to nearly perfect correlations between HR-based TL methods and HMD. Correlations between internal load and external load parameters was weaker in HSD than TD. In the light of the results of the current study, internal and external loads should not be used interchangeable and HMD seems to be appropriate to monitor TL in soccer players because its equations include both speed and acceleration values.